Evaluation of the nasolabial angle in the Indian population - Vinay Dua; Shilpa Gupta; Chanjyot Singh (Wolters Kluwer Medknow Publications, 2010)
Nasolabial angle has become the angle depicting the esthetics so has attained the prime importance in the treatment planning. Dr Jay P. Fitzgerland and Dr. Ram S. Nanda. In 1992 gave norms for Caucasian population. A radiographic cephalometric study was undertaken with 45 subjects of Indian origin to evaluate and compare with their result. The method of evaluation was according to the criteria given by Dr. Jay P Fitzergerald in AJODO 1992; 102:328-34. Significant decrease in nasolabial angle values was found in case of Indian population as compared to white adults.